Collaboration Process in Prevention of Child Marriage in Central Mamuju District - Nilmawiah, Nilmawiah; Ansar, Ansar; Ilyas, Gunawan Bata; Kurniawaty, Kurniawaty (Journal of Management and Administration Provision, 2025)
Child marriage is a problem for the government area, especially in Central Mamuju Regency. It is a common problem that requires prevention based on collaboration with several stakeholders involved in it. Governance. Research This aims to analyze the collaboration process in the prevention of marriage-age children in Central Mamuju Regency. This study uses qualitative research methods. Data collection methods include observation, in-depth interviews, and study documentation. Data sources consist of primary and secondary data. Data analysis uses interactive data analysis. As for the informants in the study, they are actors involved​ directly in the collaboration process in the prevention of wedding-age children in Central Mamuju Regency.Research results show that the collaboration process in the prevention of wedding-age children in Central Mamuju Regency can it is said Still Not yet walk with good. This is a dialogue between face, commitment in the process of collaboration, and understanding together in the prevention of wedding-age children in Central Mamuju Regency is still Not yet effective, but there is trust built​ between the actors to prevent and suppress the number of wedding-age children. As for the impact of the results so far this is in the process of collaboration in the prevention of wedding-age children in Central Mamuju Regency which has still Not yet shown significant changes.